2016
DOI: 10.1007/s11047-016-9552-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical regimes in non-ergodic random Boolean networks

Abstract: Random boolean networks are a model of genetic regulatory networks that has proven able to describe experimental data in biology. Random boolean networks not only reproduce important phenomena in cell dynamics, but they are also extremely interesting from a theoretical viewpoint, since it is possible to tune their asymptotic behaviour from order to disorder. The usual approach characterizes network families as a whole, either by means of static or dynamic measures. We show here that a more detailed study, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…It has also been observed elsewhere that the Derrida plots computed by perturbing a subset of all of the possible initial states (for example, those belonging to some attractor) can be very different from the theoretical ones [23]. The phenomena related to the peculiarities of restricting the set of states of an RBN require further studies, as the differences shown here confirm.…”
Section: Transients and Attractorssupporting
confidence: 62%
See 2 more Smart Citations
“…It has also been observed elsewhere that the Derrida plots computed by perturbing a subset of all of the possible initial states (for example, those belonging to some attractor) can be very different from the theoretical ones [23]. The phenomena related to the peculiarities of restricting the set of states of an RBN require further studies, as the differences shown here confirm.…”
Section: Transients and Attractorssupporting
confidence: 62%
“…While this might seem surprising, it should be recalled that critical states share some properties, but there may be differences. Indeed, it has already been shown elsewhere [23] that RBNs can show heterogeneous behaviors in different positions along the critical line (even maintaining critical dynamics). Figure 7b (the interpolating curve has been obtained by fitting a quadratic function to the measured points, and it is only a visual aid).…”
Section: A Bird's Eye View Of the Dynamical Behavior Of Families Of Rbnsmentioning
confidence: 75%
See 1 more Smart Citation
“…we should mention that Boolean networks are nonergodic systems, and different notions of criticality can be proposed, as discussed in [29]. The classical Derrida parameter is measured by computing the distance between initially close states, which are chosen at random, without any constraints.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by considering the downstream effect of a single flip on the input of the various Boolean functions. The choice of the most representative value of the sensitivity may be complicated [29] but, in the case of ergodic systems, the dynamic and static methods asymptotically provide the same estimate (while the effective values computed on finite numbers of cases may of course differ).…”
Section: Boolean Models Of Gene Regulatory Networkmentioning
confidence: 99%